2015
DOI: 10.1002/ab.21628
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the stability of interpersonal hostile‐dominance and its relationship with psychiatric symptomatology and post‐discharge aggression

Abstract: The relevance of interpersonal hostile-dominance (HD) to post-discharge aggression in mental health patients is unclear. This study assessed whether (1) HD is stable over time; (2) the relationship between HD and positive, negative, disorganized, and excited symptoms is consistent over time; and (3) HD is related to aggression post-discharge. Two hundred psychiatric inpatients were recruited on admission to hospital; 41 were available for follow-up at 6 months post-discharge, including 29 men and 12 women, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This study found that positive symptoms ( P = 0.031, OR = 2.01) act as a risk factor for aggressive behaviour, a finding indicated by other international studies. 28 30 The presence of positive symptoms, such as delusions, hallucinations, and excitement, is a key risk factor for aggressive behaviour. One clinical study of aggression in patients with psychosis 31 reported that hostility (which is also a positive symptom) is associated with aggression.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that positive symptoms ( P = 0.031, OR = 2.01) act as a risk factor for aggressive behaviour, a finding indicated by other international studies. 28 30 The presence of positive symptoms, such as delusions, hallucinations, and excitement, is a key risk factor for aggressive behaviour. One clinical study of aggression in patients with psychosis 31 reported that hostility (which is also a positive symptom) is associated with aggression.…”
Section: Discussionmentioning
confidence: 99%